2018
DOI: 10.1111/jsr.12797
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sleep on complex gross‐motor adaptation in adolescents

Abstract: Sleep has been shown to facilitate the consolidation of newly acquired motor memories in adults. However, the role of sleep in motor memory consolidation is less clear in children and adolescents, especially concerning real‐life gross‐motor skills. Therefore, we investigated the effects of sleep and wakefulness on a complex gross‐motor adaptation task by using a bicycle with an inverse steering device. A total of 29 healthy adolescents aged between 11 and 14 years (five female) were either trained to ride an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 52 publications
4
25
2
Order By: Relevance
“…Two accounts might explain the absence of a sleep effect on task proficiency. (1) Sleep rather stabilizes than improves gross-motor memory, which is in line with previous gross-motor adaption studies (Bothe et al, 2019; Bothe et al, 2020). (2) Pre-sleep performance is critical for sleep to improve motor skills (Wilhelm et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Two accounts might explain the absence of a sleep effect on task proficiency. (1) Sleep rather stabilizes than improves gross-motor memory, which is in line with previous gross-motor adaption studies (Bothe et al, 2019; Bothe et al, 2020). (2) Pre-sleep performance is critical for sleep to improve motor skills (Wilhelm et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Hippocampal memory reactivation during sleep is one cornerstone of the active systems consolidation theory, where coordinated SO-spindle activity route subcortical information to the cortex for long-term storage (Diekelmann & Born, 2010; Helfrich et al, 2019; Klinzing et al, 2019; Ngo et al, 2020). Quantitative markers of spindle and SO activity but not the quality of their interaction have been frequently related to motor memory in the past (Barakat et al, 2011; Bothe et al, 2019; Bothe et al, 2020; Huber et al, 2004; Morita et al, 2012; Nishida & Walker, 2007; Tamaki et al, 2008). Our results now complement the active systems consolidation theories’ mechanistic assumption of interacting oscillations by demonstrating that a precise SO-spindle interplay subserves gross-motor skill learning ( Figure 3DE ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are more studies about the role of sleep in motor ability and motor learning [12,22] at any age of life [22,23]. Particularly, an interesting report of Bothe et al [22] in 2018 showed the impact of sleep on gross motor adaptation in a group of adolescents with typical developing profile, pinpointing the role of an increase in REM sleep on cortico-cerebellar network activity that organizes dynamic aspects of movement such as motor coordination. From this perspective, we can explain the REM% reduction in our sample as a sign of the alteration in cortico-cerebellar network activity that could be considered as a cause of DCD [24].…”
Section: Discussionmentioning
confidence: 99%
“…This approach combines the reliability of standardized automatic scouring with the validity of human expert scoring and has successfully applied in earlier studies on sleep of adolescents (e.g. (63,64)). Due to technical problems, the recordings of two nights (1 x placebo condition, 1 x caffeine condition) were incomplete.…”
Section: Salivary Caffeine and Melatoninmentioning
confidence: 99%